CSR di Era Pandemi Berbasis Nilai-Nilai Bela Negara: Analisis Konten pada Situs Website Resmi Lima Badan Usaha Milik Negara - Yani Hendrayani; Uljanatunnisa Uljanatunnisa (Society, 2021)
The urgency of the COVID-19 pandemic in Indonesia continues to increase. Companies in Indonesia are now focusing on CSR programs to assist the government in accelerating the handling of COVID-19. This study aims to examine the form of social support by implementing CSR on the official website pages of 5 State-Owned Enterprises. The type of research used in this research is qualitative using a qualitative content analysis approach. Sampling used non-probability sampling method. The technique used was purposive sampling by taking samples of news content and various CSR activities on the website pages of 5 State-Owned Enterprises. The data analysis technique uses data coding using a deductive approach. The value analysis of CSR activities is implemented and implementing CSR based on the value state of defense. Otherwise, three CSR pillars, namely People, Profit, and Planet, are implemented in various CSR activities covering education, health, environment, infrastructure, community empowerment, disaster management, and special assistance to affected communities. The Result of the seven categories, the three most frequently encountered are community economic empowerment support through Micro, Small, and Medium Enterprises (MSMEs) and health support and educational support.